2015
DOI: 10.5812/jjm.27517
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Escherichia coli and Klebsiella pneumoniae Isolated From Patients in Kashan, Iran

Abstract: Background:Escherichia coli and Klebsiella pneumoniae are common human pathogens that cause a wide spectrum of infections. Antimicrobial resistance is a basic obstacle in the management of these infections which has different patterns in various regions.Objectives:In this study, the antibiotic resistance patterns and risk factors for multidrug-resistant (MDR) E. coli and K. pneumoniae were determined.Patients and Methods:In this cross-sectional study, a total of 250 isolates (134 E. coli and 116 K. pneumoniae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
8
21
2
Order By: Relevance
“…showed the highest resistance rate, 41.66%. A [34] and approximately 28.5% in community-acquired UTI [35]. Another study conducted in India revealed that the resistance rate of Klebsiella pneumoniae to ciprofloxacin was 80% [36].…”
Section: Antibiotic Nonsusceptibilitymentioning
confidence: 99%
“…showed the highest resistance rate, 41.66%. A [34] and approximately 28.5% in community-acquired UTI [35]. Another study conducted in India revealed that the resistance rate of Klebsiella pneumoniae to ciprofloxacin was 80% [36].…”
Section: Antibiotic Nonsusceptibilitymentioning
confidence: 99%
“…Klebsiella pneumoniae is one of the most important human bacterial pathogens, result to the extensive range of community and hospital acquired infections that may lead to morbidity and mortality, particularly in immunocompromised patients. [ 1 2 ] Urinary tract infections (UTIs)-induced by multidrug-resistant (MDR) K. pneumoniae isolates are a serious public health problem. The potency of many antimicrobial agents have been limited, also these bacteria are hard and expensive to cure.…”
Section: Introductionmentioning
confidence: 99%
“…These divergences require geographical surveys due to their resistance patterns and risk factors. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…In lactose media, Salmonella consumes metabolic waste from E. coli creating a mechanism of reciprocation for cooperation (Harcombe 2010). The interactions between E. coli and S. typhi may lead to infections, which may also lead to transfer of resistance to antimicrobial drugs (Moini et al 2015). The opportunistic pathogens use hierarchical quorum-sensing network to regulate virulence factor production that cooperatively benefit the population at a cost to the individual (Ron et al 2018).…”
Section: Discussionmentioning
confidence: 99%